State Oppression and Adivasi Resistance in Mahasweta Devi’s Chotti Munda and His Arrow - Bushra Mahzabeen (Crossings, 2021)
The independence movement in India against the British colonizers was driven by the hopes of freedom of speech, freedom of life, and rights over the land. However, it can be argued that the fruits of independence, which India secured in 1947 after years of struggle, have not reached every corner of its multilayered society especially to the indigenous people. Mahasweta Devi in her Bangla novel Chotti Munda Ebong Tar Tir (1980), translated into English by Gayatri Chakravorty Spivak as Chotti Munda and His Arrow (2003), exposes the hypocrisy of the West Bengal government that allows a systematic alienation of the subaltern tribes and the consequential threat of annihilation to their existence. This paper analyzes how the indigenous Munda community in the novel was forced to remain outside the narrative of national development and repeatedly experienced violence at the hands of the corrupt people in power. The aim of this paper is to discuss the hypocritical grand narrative of a national independence and how a national culture prompts marginalization and exclusion of the minority citizens in policy making in Mahasweta Devi’s novel. The paper also explores various forms of struggle and resistance on the part of the adivasi to achieve their freedom in the already independent India and the way Devi’s protagonist resists the repressive core by using the powerful cultural identity of the adivasi inhabiting the social periphery.